2021
DOI: 10.1080/01639625.2021.1899756
|View full text |Cite
|
Sign up to set email alerts
|

Racial Sympathy and Support for Capital Punishment: A Case Study in Concept Transfer

Abstract: Beliefs about race, especially racial resentment, are key predictors of public support for capital punishment and punitiveness generally. Drawing on a conceptual innovation by political scientist Jennifer Chudy, we explore the utility of transferring into criminology her construct of racial sympathy-or Whites' concern about Blacks' suffering. First, across three data sets, we replicate Chudy's finding that racial sympathy and resentment are empirically distinct constructs.Second, based on a national-level 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 84 publications
2
14
0
Order By: Relevance
“…One is that in addition to differences in the quantity of experiences with the police, differences in the quality of experiences are also likely to matter. Additionally, other dimensions of contemporary racial attitudes-such as sympathy or White identification (Chudy 2021;Hannan et al 2021;Jardina 2019) or the ignorance that protects White privilege (Drakulich and Rodriguez-Whitney 2018;Mills 2007Mills , 2011)-may also be relevant to views of police use of force.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is that in addition to differences in the quantity of experiences with the police, differences in the quality of experiences are also likely to matter. Additionally, other dimensions of contemporary racial attitudes-such as sympathy or White identification (Chudy 2021;Hannan et al 2021;Jardina 2019) or the ignorance that protects White privilege (Drakulich and Rodriguez-Whitney 2018;Mills 2007Mills , 2011)-may also be relevant to views of police use of force.…”
Section: Discussionmentioning
confidence: 99%
“… 8. We also encourage work into other potentially relevant dimensions of racial attitudes, including racial sympathy (Chudy 2021; Hannan et al 2021), White guilt (Chudy, Piston, and Shipper 2019), White nationalism (Graham et al 2021a), and White identity (Jardina 2019, 2021; Kaufmann 2019). …”
mentioning
confidence: 99%
“…A large body of criminological research has demonstrated that racial resentment—a construct imported from social psychology and political science—is a consistent predictor of policy preferences (Cullen et al., 2021). Although still recognizing the salience of racial resentment, criminologists (e.g., Hannan et al., 2022) have drawn attention to the next generation of political scientists—including those trained by some inventors of the racial resentment scale—who are moving beyond racial resentment to conceptualize and measure distinct racial attitudes that may contribute to a more comprehensive understanding of how adults in the United States think and feel about race. The inventors of these “new” racial attitudes—racial sympathy and White nationalism—build from the same scholarly tradition established by Kinder, Sanders, and their colleagues, by conceptualizing racial attitudes based on careful observations of changing social contexts regarding race and race relations in the United States.…”
Section: Racial Attitudes and Belief In Redeemabilitymentioning
confidence: 99%
“…In light of these findings, Hannan and colleagues (2022) argued that racial sympathy may be useful to import into criminal justice public opinion research. In an analysis of White respondents from the same 2019 YouGov survey used by Butler (2020) and of two MTurk surveys, Hannan et al.…”
Section: Racial Attitudes and Belief In Redeemabilitymentioning
confidence: 99%
“…In addition, the effects of gender and sexual orientation on the attitudes towards death penalty are mediated by political beliefs and empathic concerns. Many studies have indicated significant racial differences in support and use of death penalty (Applegate et al, 1994;Arthur, 1998;Baker et al, 2005;Cochran et al, 2019;Dambrun, 2007;Foglia & Connell, 2019;Hannan et al, 2021;Medwed, 2020;Unnever et al, 2008). Using cross-sectional data from the General Social Survey, 1974-2006, Dotson and Carter (2012 investigated the independent, as well as mutual, influences of race and gender on attitudes toward death penalty over time and identified significant differences by race, but not by gender.…”
Section: Literature Reviewmentioning
confidence: 99%